Contextual Wordwall Games for Number Recognition in Inclusive Kindergarten: Permainan Wordwall Kontekstual untuk Pengenalan Angka di TK Inklusif - Sinta D, Nia Aprilia Pratama; Ishartiwi; Handoyo, Rendy Roos (Indonesian Journal of Innovation Studies, 2025)
Background: Early childhood number recognition is a crucial foundation for mathematical development and life skills, yet children with learning difficulties often struggle due to a lack of engaging and inclusive teaching media. Specific background: Existing research rarely focuses on digital game-based learning tools like Wordwall in inclusive kindergarten contexts. Knowledge gap: There is limited evidence on how contextual-based Wordwall games address numeracy challenges for children with learning barriers. Aim: This study aimed to explore the application of contextual-based Wordwall educational games to support number recognition skills in kindergarten group B children with learning difficulties. Results: Using Kemmis and McTaggart’s classroom action research design, two cycles of intervention were conducted with 10 participants. Mastery levels increased from 40–50% in cycle I (average score 6.4–6.5) to 90–100% in cycle II (average score 7.3–8.1). Cognitive, affective, and psychomotor improvements were observed, including better sequencing, number-object matching, collaboration, and confidence. Novelty: This study introduces the integration of contextual Wordwall games as a digital tool for inclusive early childhood classrooms. Implications: Findings suggest that teachers can adopt contextual Wordwall games as an alternative media to create meaningful, interactive, and adaptive learning for children with learning difficulties. Highlights Children’s number recognition skills improved after contextual Wordwall game use Cognitive, affective, and psychomotor skills developed simultaneously Teachers gained a practical and replicable strategy for inclusive classrooms Keywords: Number Recognition, Contextual Learning, Wordwall Educational Games, Inclusive Kindergarten, Learning Difficulties